2016
DOI: 10.1103/physrevb.94.155155
|View full text |Cite
|
Sign up to set email alerts
|

Angle-resolved photoemission observation of Mn-pnictide hybridization and negligible band structure renormalization in BaMn2As2 and BaMn2Sb2

Abstract: We performed an angle-resolved photoemission spectroscopy study of BaMn2As2 and BaMn2Sb2, which are isostructural to the parent compound BaFe2As2 of the 122 family of ferropnictide superconductors. We show the existence of a strongly kz-dependent band gap with a minimum at the Brillouin zone center, in agreement with their semiconducting properties. Despite the half-filling of the electronic 3d shell, we show that the band structure in these materials is almost not renormalized from the Kohn-Sham bands of dens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 33 publications
4
29
0
Order By: Relevance
“…ARPES study [39] and DFT+DMFT calculations [40] have shown that the valence band of BaMn 2 As 2 mainly consists of Mn 3d x 2 −y 2 and As 4p z orbitals. The doped holes occupy the hybridized d-p orbital, whose wave function is obtained by the LCAO method, |ψ dp ,…”
Section: B Hole-doped Bamn2as2mentioning
confidence: 99%
See 1 more Smart Citation
“…ARPES study [39] and DFT+DMFT calculations [40] have shown that the valence band of BaMn 2 As 2 mainly consists of Mn 3d x 2 −y 2 and As 4p z orbitals. The doped holes occupy the hybridized d-p orbital, whose wave function is obtained by the LCAO method, |ψ dp ,…”
Section: B Hole-doped Bamn2as2mentioning
confidence: 99%
“…For this purpose, we introduce a tight-binding Hamiltonian for the valence band of BaMn 2 As 2 mainly consisting of Mn d x 2 −y 2 orbital [39,40].…”
Section: Effective Modelmentioning
confidence: 99%
“…In tetrahedral symmetry, Mn 2+ ions in a high-spin state could in fact support this scenario with one t 2g orbital (xy) being more susceptible to hybridization. Moreover, angleresolved photoemission spectroscopy (ARPES) experiments observed Mn-pnictide hybridization in BaMn 2 As 2 and BaMn 2 Sb 2 [18].…”
Section: Introductionmentioning
confidence: 99%
“…Strictly, however, half-filled systems with d 5 configuration have to be regarded as the Mott-type parent compounds, which is confirmed by the semiconducting properties of e.g. BaMn 2 As 2 [5][6][7][8][9] as well as of LaOMnAs and LiMnAs [10 and 11].…”
Section: Introductionmentioning
confidence: 99%